2010
DOI: 10.1017/s0016756810000476
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenetic and tectonic inferences from the study of the Mt Cer pluton (West Serbia)

Abstract: -The Mt Cer Pluton, Serbia, is a complex laccolith-like intrusion (∼ 60 km 2 ), situated along the junction between the southern Pannonian Basin and northern Dinarides. It intrudes Palaeozoic metamorphic rocks causing weak to strong thermal effects. Based on modal and chemical compositions, four rock-types can be distinguished: (1) metaluminous I-type quartz monzonite/quartz monzodiorite (QMZD); (2) peraluminous S-type two-mica granite (TMG), which intrudes QMZD; (3) Stražanica granodiorite/quartz monzonite (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 79 publications
(156 reference statements)
2
46
0
1
Order By: Relevance
“…10 East-West profile sketches illustrating the migration of magmatism from the upper plate (Tisza-Dacia and Rhodopes) into the lower plate (present-day Dinarides due to delamination of the lower plate (Adriatic) lithospheric mantle, possibly associated with slab break-off. Present-day geometry is that provided by the mantle tomography (Piromallo and Morelli 2003) and a by a crustal transect Miocene magmatic activity in the Dinarides The Miocene Polumir intrusion (18 Ma) is part of a larger group of S-type granitoids in the Dinarides that includes a part of the Cer intrusive (albeit within an older I-type quartz monzonite; an age around 16 Ma (K-Ar) is reported for the S-type two-mica granite; Koroneos et al 2010) and the twomica Bukulja intrusion (20-17 Ma are reported for the twomica granites; Cvetković et al 2007b). It is uncertain, however, if the somewhat older I-type Golija intrusion with high-K affinity also belongs to this same suite.…”
Section: Discussion Of Data Within the Regional Geodynamic Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…10 East-West profile sketches illustrating the migration of magmatism from the upper plate (Tisza-Dacia and Rhodopes) into the lower plate (present-day Dinarides due to delamination of the lower plate (Adriatic) lithospheric mantle, possibly associated with slab break-off. Present-day geometry is that provided by the mantle tomography (Piromallo and Morelli 2003) and a by a crustal transect Miocene magmatic activity in the Dinarides The Miocene Polumir intrusion (18 Ma) is part of a larger group of S-type granitoids in the Dinarides that includes a part of the Cer intrusive (albeit within an older I-type quartz monzonite; an age around 16 Ma (K-Ar) is reported for the S-type two-mica granite; Koroneos et al 2010) and the twomica Bukulja intrusion (20-17 Ma are reported for the twomica granites; Cvetković et al 2007b). It is uncertain, however, if the somewhat older I-type Golija intrusion with high-K affinity also belongs to this same suite.…”
Section: Discussion Of Data Within the Regional Geodynamic Contextmentioning
confidence: 99%
“…Fig. 9), Koroneos et al (2010) and Cvetković et al (2007b) proposed emplacement during the early stages of extension related to the formation of the Pannonian basin, the Bukulja intrusion being located in the footwall of a major core complex exhumed in early Miocene times (Marović et al 2007). Hence, the location of these S-type granites at the southern margin of the Pannonian basin, their Early Miocene age, and their association with core complex formation all argue for them being located in the backarc area of the W-directed subduction of the European lithosphere beneath the Carpathians, widely invoked to explain extension and magmatism in the main part of the Pannonian basin (Csontos 1995;Seghedi et al 2004).…”
Section: Discussion Of Data Within the Regional Geodynamic Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The Late Eocene-Oligocene magmatic belt evolved from K-rich trachybasalts (34 Ma) via shoshonites, calc-alkaline and high-K calcalkaline basalts (33 to 31 Ma) to alkaline basalts (28-26 Ma; Marchev et al, 2004Marchev et al, , 2005Cvetković et al, 2000;Prelević et al, 2005). The origin of this very heterogeneous magmatism has generally been explained to be related to the postcollisional collapse of the Dinaride orogen (Late Oligocene) followed by the extension in the Pannonian basin (Miocene) and in the Aegean area (Pliocene) (Cvetković et al, 2000(Cvetković et al, , 2004Koroneos et al, 2011;Prelević et al, 2005;Schefer et al, 2011;Van Hinsbergen and Schmid, 2012). It was also demonstrated that the mafic magmas resulted from the melting of depleted mantle metasomatized by earlier subduction processes.…”
Section: Regional Geological Settingmentioning
confidence: 99%